A case report of misdiagnosed fetal lung mass and review of the literature - Wang, Zongyu; Xu, Chang; He, Taozhen; Yuan, Miao (Frontiers in Pediatrics, 2023)
The patient was a male neonate, and prenatal ultrasound detected a right lung mass. He was born at term and had tachypnea and feeding difficulties after delivery. Chest X-rays and computed tomography (CT) revealed a large mass in the right chest with compression on the right lung after birth. We initially considered congenital pulmonary airway malformation (CPAM). After conservative treatment, his respiratory symptoms worsened gradually, and he required continuous supplemental oxygen. The signs could not be relieved by puncturing because the postnatal ultrasound showed a mass with anechoic microcystic spaces. Thus, in our hospital, he underwent an emergency thoracotomy and lobectomy at 14 days of age. The pathology was consistent with fetal lung interstitial tumor (FLIT). The patient remained healthy at the three-month follow-up. In addition, we reviewed the literature about FLIT and found that 23 cases of FLIT have been reported worldwide to date.